If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 4q = 5q Solving 7 + 4q = 5q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-5q' to each side of the equation. 7 + 4q + -5q = 5q + -5q Combine like terms: 4q + -5q = -1q 7 + -1q = 5q + -5q Combine like terms: 5q + -5q = 0 7 + -1q = 0 Add '-7' to each side of the equation. 7 + -7 + -1q = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1q = 0 + -7 -1q = 0 + -7 Combine like terms: 0 + -7 = -7 -1q = -7 Divide each side by '-1'. q = 7 Simplifying q = 7
| (3-y)i=4i | | -22+5x=14 | | 0.2(x-3)=0.1(x-5) | | x^2+50x+600=0 | | 6(x+1)+4=2(3x+5) | | 350x=875 | | 100=5(5+x) | | P=2(v+3)+5x | | 0g=1 | | 21-8x=3(1+6)-6 | | f(x)=4x^3-3x^2-19x+99 | | 4y^2+Xy=8 | | 0=6x^2+7x | | 10x-x=1 | | 7(4x-2)+5=28x-9 | | -2(-5+8)= | | 5r+14=86-4r | | (4x+5z)(7x-5z)= | | 49x^2-24x=0 | | 1/2x+16=4-2/3x | | 13-3y=y-7 | | tanA=.6473 | | P=2(v+3)+10 | | 45+5=s | | 3(180-x)= | | (6+3)-4= | | (6+3)+-4= | | 8n+4=22+6n | | 10x=1.2121212121 | | v+39=9v-9 | | -2(x-1)=3x-4 | | 2.4n+(-3)=-13 |